Physiotherapy treatment on Balance impairment in patients with Parkinson’s Disease : A systematic review” - P. Gawande, Rutuja; Chakwate, Mahima; Acharya, Pooja; Chavan, Harshada; Imandar, Firdous (Journal of Neonatal Surgery, 2025)
Parkinson's disease (PD) is a progressive neurological condition that significantly affects balance, movement, and total motor function, heightening the risk of falls and diminishing quality of life. Physiotherapy has become an essential intervention for alleviating balance deficits in people with Parkinson's disease, with numerous treatment modalities investigated to improve motor control and stability. This systematic study evaluates the efficacy of physiotherapy-based rehabilitation treatments, encompassing sensor-based training, virtual reality (VR) therapy, multidisciplinary rehabilitation strategies, and traditional physiotherapy methods. This review synthesizes many research to elucidate the impact of various therapies on enhancing postural control, gait stability, and functional mobility in people with Parkinson's disease. The results indicate that technology-assisted physiotherapy, cognitive-motor training, and task-specific exercises significantly enhance neuromuscular coordination and mitigate fall risk. Furthermore, the incorporation of contemporary therapeutic approaches, including vestibular stimulation, dynamic weight support, and mirror neuron therapy, has demonstrated favorable results in rehabilitation programs. Although traditional physiotherapy is fundamental in Parkinson's disease management, the integration of innovative rehabilitation methods has shown enhanced efficacy in mitigating balance deficits. This study emphasizes the necessity of a tailored and interdisciplinary rehabilitation strategy, arguing for additional clinical research to enhance physiotherapy protocols and improve patient-centered care. Categories:Neurological Rehabilitation, Physiotherapy & Rehabilitation Sciences